Discrimination and identification of azimuth using spectral shape - Shub, Daniel E.; Carr, Suzanne P.; Kong, Yunmi; Colburn, H. Steven (2008)
Monaural measurements of minimum audible angle (MAA) (discrimination between two locations) and absolute identification (AI) of azimuthal locations in the frontal horizontal plane are reported. All experiments used roving-level fixed-spectral-shape stimuli processed with nonindividualized head-related transfer functions (HRTFs) to simulate the source locations. Listeners were instructed to maximize percent correct, and correct-answer feedback was provided after every trial. Measurements are reported for normal-hearing subjects, who listened with only one ear, and effectively monaural subjects, who had substantial unilateral hearing impairments (i.e., hearing losses greater than 60dB) and listened with their normal ears. Both populations behaved similarly; the monaural experience of the unilaterally impaired listeners was not beneficial for these monaural localization tasks. Performance in the AI experiments was similar with both 7 and 13 source locations. The average root-mean-squared deviation between the virtual source location and the reported location was 35°, the average slopes of the best fitting line was 0.82, and the average bias was 2°. The best monaural MAAs were less than 5°. The MAAs were consistent with a theoretical analysis of the HRTFs, which suggests that monaural azimuthal discrimination is related to spectral-shape discrimination.